2018
DOI: 10.1038/s41598-018-27315-2
|View full text |Cite
|
Sign up to set email alerts
|

The germline mutational landscape of BRCA1 and BRCA2 in Brazil

Abstract: The detection of germline mutations in BRCA1 and BRCA2 is essential to the formulation of clinical management strategies, and in Brazil, there is limited access to these services, mainly due to the costs/availability of genetic testing. Aiming at the identification of recurrent mutations that could be included in a low-cost mutation panel, used as a first screening approach, we compiled the testing reports of 649 probands with pathogenic/likely pathogenic variants referred to 28 public and private health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
83
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 43 publications
8
83
0
2
Order By: Relevance
“…Although these pathogenic mutations were first identified in Ashkenazi Jews, BRCA1 c.5266dupC, was later described in other populations. It has already been identified in many countries of Central and Eastern Europe (Burcos et al, 2013;Gorodetska et al, 2015) and also recurrently described in the Brazilian population (Lourenço et al, 2004;da Costa et al, 2008;Fernandes et al, 2016), representing 20% of the BRCA1 pathogenic variants reported in a recent survey (Palmero et al, 2018).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Although these pathogenic mutations were first identified in Ashkenazi Jews, BRCA1 c.5266dupC, was later described in other populations. It has already been identified in many countries of Central and Eastern Europe (Burcos et al, 2013;Gorodetska et al, 2015) and also recurrently described in the Brazilian population (Lourenço et al, 2004;da Costa et al, 2008;Fernandes et al, 2016), representing 20% of the BRCA1 pathogenic variants reported in a recent survey (Palmero et al, 2018).…”
mentioning
confidence: 75%
“…There are some limitations to the present study. Unfortunately, the sample size was small, considering that c.5266dupC corresponds to 20.2% of all Brazilian BRCA1 pathogenic variants (Palmero et al, 2018), although, our samples account for patients of three Brazilian states. Nonetheless, it is the largest published study revealing a single haplotype between carriers in Brazil.…”
mentioning
confidence: 99%
“…European ancestry is most prevalent in Argentina Solano et al, 2012;Solano et al, 2017;Solano et al, 2018), Brazil (Palmero et al, 2018) and Uruguay (Delgado et al, 2011) and the sequencing results of novel and few recurrent variants are consistent with heterogeneity from this admixture. Very importantly, a warning for not blindly importing panels of hotspot genetic variants if not tested before in the local context of regional spectrum of variants.…”
Section: S E Q U E N C I N G T E C H N O L O G I E S I N L a T I N Amentioning
confidence: 67%
“…Overall results showed very few common variants in Latin America, although the substantial differences in the methodologies are a limitation. In a recent publication of the results published from sixteen laboratory groups in Brazil (Palmero et al, 2018), only five performed full sequencing of both BRCA1/2 genes (Alemar et al, 2017;Carraro et al, 2013;Fernandes et al, 2016;Maistro et al, 2016;Silva et al, 2014); the other studies include sequencing selected exons, analyzing only the BRCA1 gene and other various assays.…”
Section: S E Q U E N C I N G T E C H N O L O G I E S I N L a T I N Amentioning
confidence: 99%
“…Generating data from local and regional populations is an important factor for classification of genetic variants. Fortunately, a few reports describe genetic variant data from patients of the different countries in Latin America [4][5][6][7][8][9][10][11][12][13] . The collection and documentation of regional genetic variants are valuable in order to understand the genetic landscape of the region, which is under-represented in many United States or European variant databases.…”
mentioning
confidence: 99%